2023
DOI: 10.21203/rs.3.rs-2582833/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictive value of estimated pulse wave velocity for cardiovascular and all- cause mortality in individuals with obesity

Abstract: Background: Estimated pulse wave velocity (ePWV) has revealed excellent performance in predicting cardiovascular disease (CVD) risk. However, whether ePWV predicts all-cause mortality and CVD mortality in populations with obesity remains elusive. Methods: We performed a prospective cohort including 49,116 participants from the National Health and Nutrition Examination Survey from 2005 to 2014. Arterial stiffness was evaluated by ePWV. Weighted univariate and multivariate Cox regression was used to assess the e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…While direct associations between ePWV and the future onset of metabolic syndrome have not been extensively documented, ePWV is a surrogate marker of arterial stiffness and a pivotal predictor of cardiovascular risk [12,[26][27][28][29][30][31]. The European Society of Cardiology and the European Society of Hypertension have suggested that a carotid-femoral PWV value > 10 m/s signifies an increased cardiovascular risk [32].…”
Section: Wwwkjimorgmentioning
confidence: 99%
“…While direct associations between ePWV and the future onset of metabolic syndrome have not been extensively documented, ePWV is a surrogate marker of arterial stiffness and a pivotal predictor of cardiovascular risk [12,[26][27][28][29][30][31]. The European Society of Cardiology and the European Society of Hypertension have suggested that a carotid-femoral PWV value > 10 m/s signifies an increased cardiovascular risk [32].…”
Section: Wwwkjimorgmentioning
confidence: 99%